Complement System in Brain Architecture and Neurodevelopmental Disorders - Magdalon, Juliana; Mansur, Fernanda; Teles e Silva, André Luiz; de Goes, Vitor Abreu; Reiner, Orly; Sertié, Andréa Laurato (Frontiers in Neuroscience, 2020)
Current evidence indicates that certain immune molecules such as components of the complement system are directly involved in neurobiological processes related to brain development, including neurogenesis, neuronal migration, synaptic remodeling and response to prenatal or early postnatal brain insults. Consequently, complement system dysfunction has been increasingly implicated in disorders of neurodevelopmental origin, such as schizophrenia, autism spectrum disorder and Rett syndrome. However, the mechanistic evidence for a causal relationship between impaired complement regulation and these disorders varies depending on the disease involved. Also, it is still unclear to what extent altered complement expression plays a role in these disorders through inflammation-independent or -dependent mechanisms. Furthermore, pathogenic mutations in specific complement components have been implicated in the etiology of 3MC syndrome, a rare autosomal recessive developmental disorder. The aims of this review are to discuss the current knowledge on the roles of the complement system in sculpting brain architecture and function during normal development as well as after specific inflammatory insults, such as maternal immune activation during pregnancy, and to evaluate the existing evidence associating aberrant complement with developmental brain disorders.